DEVELOPING WORDWALL-BASED INTERACTIVE GAME MEDIA TO ENHANCE WRITING SKILLS AND MOTIVATION IN RECOUNT TEXT - Maharani, Rosy Puspa; Arianto, Fajar; Diningrat, Syaiputra Wahyuda Meisa (Jurnal Visi Ilmu Pendidikan, 2025)
This research addresses significant issues in teaching English recount text writing, including inadequate engagement tools and insufficient student motivation. The identified gaps on the existing body of knowledge reveal the lack of interactive and motivating instructional media. This study aims to develop and evaluate Wordwall-Based Interactive Game Media using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) to enhance writing skills and motivation among eighth-grade students at Sekolah Indonesia Johor Bahru. The Research and Development (RD) approach demonstrates that the interactive game media is both feasible and effective in improving students' writing abilities and boosting their motivation. Findings show that students exhibited enhanced writing performance and increased enthusiasm for learning. The implications suggest that integrating interactive game media into English instruction can significantly improve educational outcomes and student engagement. Recommendations include expanding the use of such media in similar educational settings and exploring its long-term effects on student achievement and motivation.